159 Elements of state graduated driver licensing laws across 50 states: a policy content analysis. (5th May 2020) - Sullivan, Lindsay; Asa, Niki; Xuan, Amy; Tattersall, Heather; Yang, Jingzhen
Abstract : Statement of Purpose: All 50 US States enacted Graduated Driver Licensing (GDL) laws to protect and prevent teens from injuries and death while learning to drive. However, GDL laws differ across states as there are no federally required provisions. This study describes the distribution of the content of state GDL laws in relation to five key law elements: (1) curfew restrictions, (2) passenger restrictions, (3) drug/alcohol use, (4) traffic violations, and (5) cell phone usage. Methods: A content analysis was conducted on all 50 US state GDL laws. State GDL laws were independently reviewed and analyzed by two coders. For each GDL law, the written language corresponding to each of the five key elements were coded based on the presence of the element in the state law: 1= present in state law or 0= absent in state law. Variation in the specific language used for the five key law elements across states were identified and described. Results: Most state GDL laws included specific language in relation to curfew restrictions (98%), passenger restrictions (94%), and traffic violations (86%). Fewer state laws included specific language on drug/alcohol violations (52%) and cell phone usage (76%). We found great variation in the language used in relation to the five key law elements across states, with curfew times and penalties for traffic violations varying widely across states. Conclusion: While all states have GDL laws, variations exist in the law elements included in state laws and the language used in these laws. Future research should examine how these variations in GDL laws may impact crash rates among young drivers. Significance and Contributions: This study furthers our knowledge of the content and language used in GDL laws across states as well variations in these laws from state to state.